Early palliative care and its translation into oncology practice in Canada: barriers and challenges - Fassbender, Konrad; Watanabe, Sharon M. (Annals of Palliative Medicine; Vol 4, No 3 (July 30, 2015): Annals of Palliative Medicine (Early Palliative Care I), 2015)
This article reviews the progress Canada has made integrating palliative care into oncologic practice. Key clinical practice guidelines (CPGs) have influenced and have been translated into Canadian oncology policy and operations. Comprehensive accreditation standards exist to guide oncology practice in institutional and ambulatory care settings. Common barriers and challenges are discussed: education and attitudes, compassion fatigue, terminology, paucity of research, aggressive cancer care, and organization and operational considerations. As a result, eight made-in-Canada innovations emerged and are described. Lessons learned and recommendations describe a plan for action.